ANALISIS PENGARUH PERANAN CORPORATE SOCIAL RESPONSIBILITY (CSR) PLANET 21 TERHADAP BRAND IMAGE HOTEL MERCURE TANGERANG BSD CITY - Sianti Ningsih; Rendy Sarudin (Jurnal Ilmiah Global Education, 2023)
This research was made with the aim of knowing how far the influence of the role of Corporate Social Responsibility (CSR) Planet 21 on the Brand Image of Hotel Mercure Tangerang BSD City. Based on the results examined by researchers, the average value of the variable X as a whole is 4,38 (Very High), while the average value of the variabel Y is 4,47 (Very High). Based on the results of the calculation of the T test, the results obtained are a sig of 0,00, which means that the variabel X (Corporate Social Responsibility (CSR)) has an effect on  Brand Image (Y). The coefficient of determination test (R2) obtained a result of 0,556 so it can be concluded that the Y varibable can be explained by the Y variable of 55,6%.